(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Blepharoptosis has a significant impact on patient functional status and may cause poor visual development in childhood and correction of congenital ptosis is one of the difficult challenges the ophthalmologist faces. Several surgical techniques were used for correction. The selection of one technique over another depends on several factors including the experience and comfort level of the surgeon with various techniques, the severity of ptosis and the degree of levator function. Objective:To Evaluate Whitnall sling procedure for moderate to severe congenital blepharoptosis with fair to poor levator function as a good choice to those whom frontalis sling procedure was there only option. Methods:Twenty five patients with different types of congenital blepharoptosis of moderate to severe degree and poor to fair levator function were received in Alwasity Hospital for Reconstructive Surgery and treated with Whitnall sling procedure. The results were evaluated according to the following criteria; Good: where the ptotic lid lies within 1 mm of normal lid position (1 mm below superior limbus) in primary gaze position. Moderate: postoperative lid position drooped more than 1 mm of normal lid position but maintained above the pupil. Poor: post operative lid position drooped to obscure the visual axis in primary gaze position. Results :20 cases (80%) were having good results, 5 cases had moderate results (20%). There were no poor results. There was no need for additional tarsectomy in our cases. Conclusion: Whitnall sling procedure is a good choice for cases lying in the overlap zone between it and the frontalis sling procedure whenever the surgical indications and procedure of choice were concerned. Keywords: blepharoptosis, congenital lid ptosis, whitnal sling